KHOTBAH SEBAGAI PRAKSIS MISSIO DEI: MENUJU KERANGKA KONSEPTUAL HOMILETIKA EVANGELISTIK - Ayub Sugiharto; Etni Grace Andi Yusuf; Reva Grace Celine; Welly Sigo (Jurnal Penggerak, 2026)
This study proposes a critical reconstruction of preaching as an evangelistic strategy by synthesizing homiletical and missiological frameworks within the missio Dei paradigm. It addresses the long-standing disciplinary fragmentation between homiletics and missiology. This fragmentation signals a crisis of homiletical identity, manifested in two forms: ecclesial introversion—namely, an excessive inward focus on congregational maintenance—and pragmatic functionalism, which reduces preaching to a mere instrument for mobilizing church activities. Such a condition is profoundly detrimental to the contemporary church, as it results in kerygmatic stagnation.  This research employs a qualitative approach with a systematic literature review (SLR) design based on the PRISMA protocol. The data consist of scholarly publications from the period 2011–2025, analyzed using a thematic analysis approach. The urgency of this research stems from the necessity of radical integration to prevent preaching from losing its prophetic edge and devolving into mere moralistic rhetoric in a fragmented public square.  The findings indicate: (1) a conceptual gap between homiletics and missiology; (2) the absence of a systematic formulation of preaching as an evangelistic praxis within the missio Dei; and (3) the dominance of descriptive approaches in contemporary homiletical studies. This research culminates in a novel integrative model that bridges the gap between textual fidelity and missional relevance, offering a transformative praxis for the contemporary church.